Physical Activity Recommendations in South America: A Decolonial Analysis; [Recomendaciones de Actividad Física en América del Sur: Un Análisis Decolonial] - Soto-Lagos, R (Brazilian Society of Physical Activity and Health, 2025)
Objective: This article analyzed official physical activity (PA) recommendations in South American countries, particularly regarding the guidelines and concepts of PA, health, and population. Methods: The research is documentary and exploratory. The primary sources are 10 documents from the Ministries of Health of Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Peru, Uruguay, and Venezuela concerning public policies on PA promotion and health promotion. The data analysis was based on a qualitative approach within social research, from a decolonial theoretical perspective. Results: The results showed that the analyzed guidelines reproduce the multicausal ex-planatory model of health-disease processes and that the recommendatory-prescriptive approach for a medicalized PA prevails. These are marks of epistemological-sanitary colonialism. The data indicate that the identified South American countries have been importing and translating, in their own way, conservative references from the global north, that do not necessarily dialogue with the continent’s socio-sanitary needs. Conclusion: In this sense, one way to locate alternative counter-references to the hegemonic logic, based on local realities, is to follow the premises of the Latin American field of Collective Health and the Critical Epidemiology of Bodily Practices. © 2025: Priscilla de Cesaro An-tunes, Heitor Martins Pasquim, María Rosa Corral-Vázquez, Tatiana Castillo, Rodrigo Soto-Lagos, Fernanda Ramos Parreira, Leonardo Trápaga Abib, Claudia Cortés-Garcia, María Laura Pagola, Edwin Alexander Canon-Buitrago.